Influencia De Un Programa Basado En El Juego Y El Juguete Para El Fomento De Las Habilidades Motrices Básicas (2015)
This research project is called "influence of a program based on play and toys for the promotion of basic motor skills." A quantitative approach with a quasi-experimental control group design was used for is development, which guided the implementation of the pre-test, the program, and the post-test. And thus identify the relevance and effectiveness of the program in relation to the motor skills of children. The test that was taken for the collection of data was validated and developed by Cesar Vargas Victoria in 2004. The program of games and toys was designed to promote gross motor skills, being the toy the main tool taken by the class. The study population were children of first grade from the educational institution Teresita Montes located in the city of Armenia. Through the process results, it was significantly concluded that the use of games and toys for teaching in the early ages is a tool or resource that supports the physical educator for the planning and execution of new proposals in order to strengthen the development of skills.